Hypoglycaemia monitoring in a medical receiving ward. Issue 1 (25th November 2015) - Ellis, Ryan
Abstract: It has been suggested that current care for diabetes inpatients remains inadequate and that greater attention is required for high quality management. In this project the aspect of hypoglycaemia was studied in a busy medical receiving ward at the Glasgow Royal Infirmary. A large proportion of inpatients have diabetes and episodes of hypoglycaemia experienced by this population can delay discharge and indeed be detrimental to health. Thus it is important from both an organisational and patient perspective to manage this population well. In this project BM machine data was analysed to identify patients who were hypoglycaemic. These patients were then tracked down to study the subsequent management and compared this against recommended guidance. Following this an intervention was made to promote identification, management, documentation, and prevention of hypoglycaemia. This was deliberately a simple intervention involving discussions with staff and provision of basic documented guidance next to every BM machine. In the first phase 17 patients were identified and in a second and third phase 16 patients each time were further identified. Patients in the study were both type 1 and type 2 diabetics. Initial results in phase I were compared to results in phase II and III respectively. This intervention produced significant improvements in management with correct monitoring of low BMs (i.e. upon identification of low BM repeat within 1 hour) improving from 47% to 100% (for Phase II and III). Also, recording of preventative measures of hypoglycaemia improved from 35% to 88% and 94% with an improvement from 24% to 69% and 75% in recording of treatment given if needed. In conclusion, the study successfully demonstrated that simple measures can significantly improve the quality care of inpatient diabetic patients in relation to hypoglycaemia management.